A interlocução dialógica na política de extensão: uma análise do programa "UFPB no seu município" - Barbosa, Emerson Lopes (2023)
This research presents a study on the extension network of the program "UFPB no seu município," aiming to map its characteristic elements and validate the concept of dialogic interlocution. The research used a qualitative and immersive approach to identify established relationships, compare the level of interactions, evaluate the impacts on micro-regions, investigate local development actions, and analyze evidence of promoting a culture of social impact. The research showed that the program's actions have brought significant benefits to local communities, contributing to improving their quality of life. Possible measures for local development were identified, and the importance of "dialogic interlocution" was emphasized as a means to establish more collaborative inter-institutional/inter-sectoral relationships between educational institutions and local communities, highlighting the formulated immersive methodology and its replicability in other educational institutions. The research contributed to strengthening university extension as a process of joint knowledge construction and promotion of social transformation. However, the research recognizes limitations and suggests future research to improve university extension practices and strengthen partnerships between academia and communities.